Temperature-driven phase transformation of Ca-rich boron waste into CaB2O4: Investigation of microstructure, crystallinity and thermal characteristics - Ceylan, Iremnur; Cicek, Bugra (ELSEVIER SCIENCE SA, 2022)
Large-scale mining and mineral processing, as well as increasing industrialization, generate a significant volume of boron wastes (BWs), necessitating waste recycling management. This research proposes a conceptual framework for circular production design based on the increased utilization of commercially valuable BWs including large amounts of B2O3, CaO, and MgO. In this study, BW is a non-calcined waste, whereas BW40, BW50, BW60 and BW90 are boron wastes calcined at 400 ?C, 500 ?C, 600 ?C and 900 ?C, respectively. Chemical, structural, thermal, and morphological characteristics and alterations depending on the calcination temperatures of BWs are investigated using XRF, XRD, FTIR, TG-DTA, and SEM techniques. BW which is non-calcined boron waste comprises Ca[B(OH)(4)](2).2H(2)O and HCaBO3 crystalline phases, whereas BW40 treated at 400 ?C has HCaBO3 and CaCO3 crystalline phases as well as amorphous structure. CaCO3 and Ca2B2O5 crystalline phases and amorphous structure are present in the BW50 and BW60 samples, calcined at 500 and 600 ?C. At 900 ?C, all phases were transformed into Ca2B2O5 and CaB2O4 crystalline phases. We demonstrated that BW40, BW50, and BW60 have comparable chemistry and morphologies, but increasing calcination temperature to 900 ?C resulted in a fundamentally different microstructure.
Keywords: Boron waste; Calcination process; Thermal decomposition; Phase transformation; Calcium metaborate; CALCINED COLEMANITE; BORATE; TILE; NANOPARTICLES; CERAMICS; BEHAVIOR; MORTAR; SYSTEM; Materials Science